(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article examines the features of the formation of public spaces in the urban environment. They are an important means of improving the physical qualities of the environment and centers of social activity of the population. An overview of modern research on public spaces related to socio-cultural processes is provided. Public spaces have undergone a long process of evolution: from the agora to the modern open social space. Public spaces of the city are centers of social interaction of the population, they act as an element of the functional-spatial organization of the environment and socio-cultural center. It is noted that several different aspects influence the parameters of public space and social contacts between people: the features of the location of surrounding buildings, the overall dimensions of the street, the availability of infrastructure, transport accessibility, recreational areas, population density, etc. Scientific research on the sociology of the city is directly related to the physical features of the urban environment. The quality of public spaces and the activity of their use by city residents depends on the variety of behavioral scenarios. Planning and spatial characteristics of public spaces form several main types: a linear type of space, which has a deep and frontal opening; a local type is a semi-closed or closed space, limited by block development; open space is represented by areas of the environment free from development: squares, parks, squares, etc. According to each of these types, examples of public spaces in different cities of Ukraine and their impact on the development of socio-cultural processes in the environment are considered. The article states that an increase in the number of public spaces in the city contributes to the formation of a healthy active environment in which there is a place for all segments of the population.